Proceso de ASC - NECESIDAD DE CRITERIOS CONSTANTES DE ESTANDARES PROBATORIOS EN CASOS DE VIOLACIONES DE DERECHOS HUMANOS ANTE LA CORTE INTERAMERICANA DE DERECHOS HUMANOS. (2022)
This paper addresses the different standards of proof that have been traditionally proposed by the doctrine, in addition to the main criticisms that have been made of these systems; the way in which the Inter-American Court of Human Rights has resorted to these criteria in various decisions of massive human rights violations -in view of the fact that its rules of procedure do not expressly embrace this concept-; and finally, the way in which the standard of 'preference of good explanations not defeated' proposed by Rodrigo Coloma, could contribute to the determination of the truth and the reduction of the Court's discretion in the resolution of these cases.